Resiliensi Akademik di SMP Negeri 25 Kota Jambi Setelah Menghadapi Situasi Pandemi - Henni Twentyona Anjelyta (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2022)
The situation faced recently in society has made many changes that have created new challenges that refer to pressure, the same is felt by students in the academic field. The purpose of the study was to describe the level of academic resilience of students at SMP Negeri 25 Jambi City after facing a pandemic situation. This research uses descriptive method with quantitative research type. The data collection technique used a questionnaire while the data analysis technique used the percentage technique. The results showed that the data obtained were that the overall academic resilience of students was in the high category with a percentage (69.46%), which means that students have a high capacity for dealing with pressure in the academic field. The results of this study are expected to have implications for guidance and counseling, namely to make this research an illustration in the provision of counseling guidance services to students, both classical, group and individual services.